2002
DOI: 10.1007/s00210-002-0534-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of noradrenaline transporter in response to prolonged exposure to ketamine

Abstract: We previously reported that the intravenous anaesthetic ketamine acutely inhibits the activity of the noradrenaline transporter (NAT) by acting on a site partly overlapping the desipramine binding site. Here we report the effects of a prolonged exposure to ketamine on the functional activity and number of NAT and its mRNA in cultured bovine adrenal medullary cells. Treatment of cells with ketamine (10-1000 microM) for 1-24 h resulted in a transient decrease and subsequent increase in [(3)H]noradrenaline (NA) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Given that no specific mammalian transporter for adrenaline has been identified, and that NAT has an affinity for and can efficiently transport not only noradrenaline but also adrenaline (Lorang et al 1994;Paczkowski et al 1999), these results suggest that, in the normal human adrenal medulla, NAT expressed in adrenergic chromaffin cells is responsible for the uptake of both adrenaline and noradrenaline. This hypothesis is supported (1) by the early work of Kent and Coupland (1981) who have demonstrated that, after intravenous injection of 3 [H] noradrenaline and 3 [H] adrenaline in mice, adrenergic cells of the adrenal medulla actively incorporate the radioisotopes and (2) by more recent work by Hara et al (2002) who have shown the uptake of 3 [H] noradrenaline in an antidepressant-sensitive manner in acutely isolated bovine adrenal medullary cells.…”
Section: Discussionmentioning
confidence: 76%
“…Given that no specific mammalian transporter for adrenaline has been identified, and that NAT has an affinity for and can efficiently transport not only noradrenaline but also adrenaline (Lorang et al 1994;Paczkowski et al 1999), these results suggest that, in the normal human adrenal medulla, NAT expressed in adrenergic chromaffin cells is responsible for the uptake of both adrenaline and noradrenaline. This hypothesis is supported (1) by the early work of Kent and Coupland (1981) who have demonstrated that, after intravenous injection of 3 [H] noradrenaline and 3 [H] adrenaline in mice, adrenergic cells of the adrenal medulla actively incorporate the radioisotopes and (2) by more recent work by Hara et al (2002) who have shown the uptake of 3 [H] noradrenaline in an antidepressant-sensitive manner in acutely isolated bovine adrenal medullary cells.…”
Section: Discussionmentioning
confidence: 76%
“…1998). In stark contrast, exposure of bovine adrenal medullary cells to ketamine for longer than 3 h increases NE uptake (Hara et al . 2002; Table 2).…”
Section: Regulation Of the Net By Other Drugsmentioning
confidence: 99%
“…The effects of ketamine are modestly attenuated in the presence of the RNA polymerase inhibitor, actinomycin D, and blocked in the presence of the ribosomal protein synthesis inhibitor cycloheximide. Following a 24 h incubation with ketamine, NET mRNA expression increases (Hara et al . 2002).…”
Section: Regulation Of the Net By Other Drugsmentioning
confidence: 99%
“…The increase in systolic and diastolic pressure in animals, as well as in man, is mainly due to enhanced cardiac output (Domino et al, 1965;Virtue et al, 1967;Schwartz & Horwitz, 1975). Moreover, A number of investigators have reported that ketamine suppresses [ 3 H]NA uptake in various sympathetic nervous tissues (Taube et al, 1975;Azzaro & Smith, 1977;Garty et al, 1990;Graf et al, 1995) and the adrenal medulla (Hara et al, 1998;Hara et al, 2002). Local administration of ketamine was also found to induce an increased norepinephrine (NE) levels in dialysate in anesthetized cats (Kitagawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%